2008
DOI: 10.1243/09544054jem931
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrary Lagrangian Eulerian analysis on cutting with a honed tool

Abstract: A thermo-elasto-viscoplastic two-dimensional finite element analysis of the effects of different edge radii on the mechanics of orthogonal metal cutting is presented. The shear stress distribution was used to quantify the stagnation point as well as the minimum chip thickness needed to form a chip when using a honed cutting edge. The determined location of the stagnation point using the shear stress distribution agrees well with location calculated using the velocity profile in the vicinity of the cutting edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…However, the workpiece material that flows towards the cutting edge is forced to split into two parts, one forming the chip and the other forming the new surface on the workpiece material. The location of the stagnation point, which has been reported to have an important role not least on the plastic strains in the newly created surface (Nasr et al 2007, Kishawy et al 2008, was found to move upwards with increasing cut-off value. This counteracted the increase in feed force resulting from increased friction.…”
Section: Cutting Forcesmentioning
confidence: 80%
See 1 more Smart Citation
“…However, the workpiece material that flows towards the cutting edge is forced to split into two parts, one forming the chip and the other forming the new surface on the workpiece material. The location of the stagnation point, which has been reported to have an important role not least on the plastic strains in the newly created surface (Nasr et al 2007, Kishawy et al 2008, was found to move upwards with increasing cut-off value. This counteracted the increase in feed force resulting from increased friction.…”
Section: Cutting Forcesmentioning
confidence: 80%
“…Umbrello et al (2007) and Umbrello (2008) performed a sensitivity study to investigate how the constants used in the J-C material model for AISI 316L and Ti6Al4V alloys influence simulated cutting forces, temperature, chip morphology and in the former case the residual stresses. Kishawy et al (2008) studied the influence of edge radius in orthogonal cutting of AISI 4140 by evaluating the cutting forces, chip thickness, temperature and stagnation point using an FE model in which a J-C material model was used. A J-C material model was also used by Woon et al (2008) to study the effect of edge radius on contact phenomena in micro-cutting of AISI 1045.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to eliminate these problems, some authors have developed a new Arbitrary Lagrangian-Eulerian formulation which enables the mesh to deform freely on its free boundaries (Lagrangian part) and the material to flow without distortion through the mesh (Eulerian part). 918 After a phase of mesh adaptation, especially the chip, the ALE makes it possible to simulate a stabilized cutting situation. Unfortunately, the mesh stabilization phase very often leads to calculation errors due to mesh distortion at the beginning of the simulation.…”
Section: Introductionmentioning
confidence: 99%